Investigation of the lubrication system in a vehicle axle: Optimization and experimental validation. (July 2019) - Peng, Qianlei; Zhou, Chi; Gui, Liangjin; Fan, Zijie
Transmission efficiency is the main concern in the design of lubrication systems for gear transmission systems, such as the vehicle axle. This paper presents an optimization method to reduce the churning loss and improve the transmission efficiency in an axle based on computational fluid dynamics and the response surface method. A simplified model was applied to determine the optimal solutions to reduce the churning loss of the wheel. The response surface models were constructed based on the numerical and orthogonal experiments to approximate the relationship between the related structures and the churning loss. A multi-objective optimization model was developed to reduce the churning loss at speeds of 50 and 90 km/h. The multi-objective optimization method of non-dominated sorting genetic algorithm-II was applied to determine the Pareto front of the optimal solutions for the churning loss. A comparative experiment was conducted to validate the optimal effect. The measurements indicate the churning loss in the optimal axle was 10.4–12.3% lower than that in the original axle, and the oil temperature in the optimal axle was approximately 2.1°C lower than that of the original axle.